Predictors of Memory Deficits in Adolescents and Young Adults with Congenital Heart Disease Compared to Healthy Controls - Pike, Nancy A.; Woo, Mary A.; Poulsen, Marie K.; Evangelista, Wendy; Faire, Dylan; Halnon, Nancy J.; Lewis, Alan B.; Kumar, Rajesh (Frontiers in Pediatrics, 2016)
Introduction: Adolescents and young adults with congenital heart disease [CHD] show a range of memory deficits, which can dramatically impact their clinical outcomes and quality of life. However, few studies have identified predictors of these memory changes. The purpose of this investigation was to identify predictors of memory deficits in adolescents and young adults with CHD after surgical palliation compared to healthy controls. Method: 156 adolescents and young adults [80 CHD and 76 controls; age 14-21 years] were recruited and administered an instrument to assess memory [Wide Range Assessment of Memory and Learning 2nd Edition – general memory index (GMI) score] and completed questionnaires that measure anxiety, depression, sleepiness, health status, and self-efficacy. Descriptive and non-parametric statistics were used to assess group differences, and logistic regression to identify predictors of memory deficits. Results: CHD subjects consisted of 58% males, median age 17 years, 41% Hispanic, and medians of 2 previous heart surgeries and 14 years since last surgery. Memory deficits [GMI < 85] were identified in 50% CHD compared to 4% healthy controls [median GMI 85 vs. 108, p <0.001]. Of GMI subscale medians, CHD subjects had significantly worse memory performance vs. healthy controls [verbal 88 vs. 105, p <0.001; attention 88 vs. 109, p<0.001; working memory 86 vs. 108, p <0.001]. No significant differences appeared between groups for visual memory. Multiple clinical and psychosocial factors were identified which were statistically different on bivariate analyses between the subjects with and without memory deficits. By multivariate analysis, male gender, number of surgeries, anxiety, and self-efficacy emerged as independent predictors of memory deficits. Conclusion: Adolescents and young adults with CHD, more than a decade since their last surgery, show significant verbal, attention and working memory deficits over controls. To enhance patient self-care, clinicians should explore ways to reduce anxiety, improve self-efficacy, and increase use of visual patient education material, especially in CHD males.